Safety, Tolerability, and Pharmacokinetics of the Mineralocorticoid Receptor Modulator AZD9977 in Healthy Men: A Phase I Multiple Ascending Dose Study. Issue 2 (30th October 2019) - Whittaker, Andrew; Kragh, Åsa M.; Hartleib‐Geschwindner, Judith; Albayaty, Muna; Backlund, Anna; Greasley, Peter J.; Heijer, Maria; Kjaer, Magnus; Forte, Pablo; Unwin, Robert; Wernevik, Linda; Ericsson, Hans
Abstract : Excessive activation of the mineralocorticoid receptor (MR) underlies the pathophysiology of heart failure and chronic kidney disease. Hyperkalemia risk limits the therapeutic use of conventional MR antagonists. AZD9977 is a nonsteroidal, selective MR modulator that may protect nonepithelial tissues without disturbing electrolyte balance. This phase I study investigated the safety, tolerability, pharmacokinetics, and pharmacodynamics of multiple oral doses of AZD9977 in healthy volunteers. Twenty‐seven male participants aged 23–45 years were randomized 3:1 to receive oral AZD9977 or placebo for 8 days (with twice‐daily dosing on days 2–7), in dose cohorts of 50, 150, and 300 mg (AZD9977, n  = 6 per cohort; placebo, n  = 3 per cohort). Adverse events occurred in 4 of 18 participants receiving AZD9977 (22.2%) and 6 of 9 receiving placebo (66.7%), all of mild or moderate severity; none were serious or led to withdrawal. AZD9977 was rapidly absorbed, with median time of maximum concentration of 0.50–0.84 hours across dose groups. Area under the curve and maximum concentration were approximately dose proportional but elimination and accumulation terminal half‐life increased with dose. Steady‐state was reached after 3–4 days, with dose‐dependent accumulation of 1.2–1.7‐fold. Renal clearance was 5.9–6.5 L/hour and 24–37% of AZD9977 was excreted in the urine. Serum aldosterone levels increased dose dependently from days −1 to 7 in participants receiving AZD9977, but serum potassium levels and urinary electrolyte excretion were unchanged. AZD9977 was generally well‐tolerated with no safety concerns. Exploratory outcomes suggested reduced hyperkalemia risk compared with MR antagonists. These findings support further clinical development of AZD9977.